THE EFFECT OF INTERNSHIPS ON STUDENTS’ SATISFACTION WITH THEIR NURSING EDUCATION - Karabulutlu, Elanur Yılmaz; Turan, Gülcan Bahçecioğlu; Oruç, Fatma Gündüz (My University, 2020)
Aim: This study aims to determine the effect of nursing internships on nursing students’ satisfaction with theirnursing education.Methods: The study population for this research comprised 321 nursing interns studying in the Nursing Facultyat Ataturk University between May and June 2017. The study sample included 285 students who agreed toparticipate in the study between these dates. The research data were collected using Personal Information Form,the Nightingale Internship Program Evaluation Scale (N-IPES) and the Student Satisfaction Scale-Short Form(SSS-SF). The research data were evaluated using arithmetic mean, standard deviation, frequency, percentile andcorrelation analysis through the SPSS package program.Results: The mean age of the participating students was 22.4 ± 1.17 years, 70.2% of them were female, 49.5%were regular high school graduates, and 63.5% willingly selected the nursing profession. A statistically significantand positive relationship was found between students’ total scores on the N-IPES and SSS-SF, and also betweenall of their mean scores on the subscales of these two scales, except the subscale of participation in decisions(p<0.05).Conclusion: Internships were found to increase students’ satisfaction with nursing education.
Keywords: Eğitim; Eğitim Araştırmaları; Sağlık Bilimleri ve Hizmetleri; Hemşirelik